Against All Enemies : Max Moore #1 - Clancy, Tom, 1947-; Telep, Peter, 1965- (New York : G.P. Putnam's Sons, 2011)
After a vicious Mexican drug cartel joins forces with the Taliban, ex-Navy SEAL and current CIA operative Maxwell Moore and his team must spring into action to protect the United States from unprecedented terror and destruction.
Keywords: Suspense fiction; Adventure fiction